Enhanced Fractional Acoustic Vortices by an Annulus Acoustic Metasurface with Multi‐Layered Rings. Issue 9 (26th July 2020) - Luo, Yanchun; Jia, Yurou; Yao, Jie; Wu, Dajian; Liu, Xiaojun
Abstract: An annulus acoustic metasurface (AAM) with multi‐layered rings is proposed to achieve the enhanced fractional acoustic vortices (FAVs). It is found that the enhancement of the transmitted FAV through the AAM is sensitive to the radial interval between adjacent ring‐structures. A greatly enhanced FAV is theoretically obtained by the optimized AAM. Then finite element models based on composite labyrinthine structures are established and the generation of the enhanced FAV is confirmed by simulations. Furthermore, the optimized AAM samples are fabricated and experimentally generate the enhanced FAV with topological charge of 1.5. The FAV generated by the optimized AAM with three‐rings is ≈5.4 times stronger than that generated by the classical AAM with one‐ring. Finally, experimental results show that the greatly enhanced FAV can capture micro‐particles and rotate a sound absorbing disk easily. The greatly enhanced FAV by the AAM may be more efficient for the micro‐particle manipulation, edge‐detection image, and acoustic communication. Abstract : An annulus acoustic metasurface (AAM) with multi‐layered rings is proposed to achieve the enhanced fractional acoustic vortices (FAVs). The greatly enhanced FAVs are predicted theoretically and verified by simulations and experiments. Finally, the enhanced FAV generated by the AAM is used to realize the micro‐particles capture and the rotation of the sound absorbing disk experimentally.